The Van Microplate: A New Microcontinent at the Junction of Iran, Turkey, and Armenia - Azizi, Hossein; Tsuboi, Motohiro (Frontiers in Earth Science, 2021)
In northwestern Iran, magmatic activity occurred during three main intervals: The Cretaceous, Eocene, and Miocene-Quaternary. The first two phases of magmatic activity are more consistent with arc-type magmatism on an active continental margin; whereas the last phase, which has calc-alkaline and alkaline affinities, shows more similarity to postcollisional magmatism. Magmatic belts are mostly situated in the northern and eastern parts of the Oshnavieh–Salmas–Khoy ophiolite belt (OSK-Ophiolite) in northwestern Iran. The OSK-Ophiolite is known as the Neotethys, an ocean remnant in northwestern Iran, and extends to eastern Turkey and surrounds the Van area. This configuration shows that the Van microplate and surrounding ocean have played an important role in the evolution of magmatic activity in northwestern Iran, eastern Turkey, and the Caucasus since the Cretaceous. The Van microplate is situated among the Arabian plate to the south, northwestern Iran to the east, and Armenia to the north. The subduction of the northern branch of the Neotethys oceanic lithosphere beneath southern Eurasia has been critical in flare-up magmatism in the southern Caucasus since the Late Cretaceous. Considering the Van area as a new microplate makes understanding the geodynamic evolution of this area easier than in the many tectonic models that have been suggested before. When regarding the Van microplate, the main suture zone, which is known as the Bitlis–Zagros zone, should be changed to the Zagros–Khoy–Sevan–Akera suture zone, which extends to the eastern and northern Van microplate and western Iran.